Risks of exposure to Covid-19 among Primary Health Care professionals in a municipality in the State of São Paulo (Research, Society and Development, 2024)
Gathering information on the epidemiology of exposure risks for professionals working in Primary Health Care is very relevant and can have significant impacts on the production of healthcare and the development of specific action plans to protect healthcare workers. Based on this question, this study aimed to investigate the risks of exposure to Covid-19 among professionals working in PHC health services in a municipality in the State of São Paulo. Data collection, from December 2021 to June 2022, took place online and in person using an OPS form adapted for PHC. 424 workers from all 17 UBS in the city participated, of which 66.8% reported direct contact with those infected; 69.9% reported knowing the five recommended moments for hand hygiene, only applying them when possible; 63.3% reported availability of protective equipment, although 36.4% indicated that they did not have all the necessary equipment, with 78% indicating that they only used disposable gloves; around 29.3% reported having suffered accidents with exposure to biological liquids and/or secretions from the patients' respiratory tract; 12.5% ​​mentioned that accidents occurred due to fluid splashing on the mucous membranes of the eyes.